The motives of the Sudanese citizen's use of YouTube and the gratifications achieved from it sample of citizens of Khartoum State for the year 2023 - Mohammed, Badereldin Ali Hamed (Arab Journal for Sciences and Research Publishing, 2023)
The study belongs to the analytical descriptive research, and the researcher used the media survey method for an available sample of 350 citizens of Khartoum state, and the researcher used the questionnaire tool. This study aimed to identify the motives of the Sudanese citizen's use of YouTube and to identify the habits and patterns of the Sudanese citizen's use of YouTube and to reveal the rate of Sudanese citizen's use of YouTube. The results showed that social news is the most preferred type of news by the Sudanese citizen. The study confirmed that the Sudanese citizen’s use of YouTube made it easier for him to shop and buy. The study indicated that YouTube helped the study sample to forget work problems. Always trust the information provided by YouTube.
Keywords: motives; YouTube; gratifications; Sudanese citizen